Nasopharyngeal angiofibroma: Our experience and literature review - Martins, Mariane Barreto Brandão; de Lima, Francis Vinicius Fontes; Mendonça, Carlos Alberto; de Jesus, Eduardo Passos Fiel; Santos, Arlete Cristina Granizo; Barreto, Valéria Maria Prado; Santos, Ronaldo Carvalho, Júnior (International Archives of Otorhinolaryngology, 2013)
Introduction: Juvenile nasopharyngeal angiofibroma is a rare, highly vascular, and histologically benign tumor, generally observed in male adolescents. It shows very aggressive behavior due to local invasiveness and is associated with various symptoms. Juvenile nasopharyngeal angiofibroma originates in the sphenopalatine forame, causing epistaxes and nasal obstruction. Objective: To retrospectively describe our experience in the diagnosis and treatment of patients with juvenile nasopharyngeal angiofibroma. Scientific drawing: Retrospective, descriptive study conducted after approval from the Ethics Committee of the Federal University of Sergipe (protocol 0114.0.107.000 -11).Methods: We analyzed findings in 20 patients who underwent surgery between 2004 and 2011. Factors analyzed include patient age and gender, symptoms, stages, treatment, length of surgery, intraoperatory bleeding, postoperative need for nasal tampons, hospitalization time, complications, and tumor recurrence. Results: Patients were aged 10–29 years. All patients were treated surgically, including 17 who underwent endoscopic surgery. The mean operation time was 120 min, and the mean bleeding volume was 300 mL. Seventeen patients required clamping of the external carotids and tumor embolization. Conclusion: Endoscopic surgery alone or with other conventional techniques was safe for the treatment of angiofibromas of different stages.
Keywords: angiofibroma; embolization; therapeutic; epistaxis